Creative living : (Glencoe/ McGraw- Hill, 1994)
Text Book: Unit 1 - Focus on youUnit 2 - Your family and friendsUnit 3 - Child care and developmentUnit 4 - Foods and nutritionUnit 6 - Clothing and textilesUnit 7 - Housing and living